Different pregnancy outcomes in patients with systemic lupus erythematosus treated with belimumab. (January 2023) - Lai, Yupeng; Li, Bin; Huang, Jiaming; Du, Jingning; Yue, Mengli; Shen, Xin; Liu, Xingjiao; Huang, Lingfeng; Lin, Jiehua; Yang, Aicheng; Wang, Meiying
Objectives: Systemic lupus erythematosus (SLE) predominantly occurs in women of child-bearing age. Selecting drugs for pregnant SLE patients has always been a difficult choice. Although there have been several reports of safety of belimumab in SLE patients during pregnancy, the data are far from sufficient. Methods: We report on 4 cases of belimumab exposure in pregnant SLE patients. We also summarized 6 case reports and case series which were previously published. Further, we compared the different outcomes among SLE patients and their babies who continued with belimumab during pregnancy with those who discontinued belimumab in early pregnancy. Results: Two cases discontinued belimumab in the early pregnancy, while the other two received belimumab until the late pregnancy. All the four women tolerated belimumab. Newborns have all developed normally and continue without complications during 1 year of follow-up. Conclusion: In this small case series, we found that belimumab was well tolerated in pregnant SLE patients. There were no safety signals for the mothers or their babies.